2007
DOI: 10.1016/s0828-282x(07)70787-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute reversible left ventricular dysfunction secondary to alcohol

Abstract: A 48-year-old woman presented to the emergency department with confusion and shortness of breath. She admitted to an eight-year history of the ingestion of more than 600 mL of vodka per day. Within the month before presentation, she had increased her alcohol intake by drinking a large glass of 70% ethanol per day.Before this medical admission, the patient had two previous admissions for acute pancreatitis due to ethanol abuse. On both occasions, she had normal cardiac enzyme levels and no evidence of cardiac d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In fact, it is well known that LV function begins deteriorating before the patient becomes symptomatic 13,14,15 , and that an early withdrawal of alcohol consumption may improve significantly the prognosis. However, although it is demonstrated that alcohol is related to DCM, the real correlation between specific doses of ethanol, genetic susceptibility and cardiomyopathy development still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is well known that LV function begins deteriorating before the patient becomes symptomatic 13,14,15 , and that an early withdrawal of alcohol consumption may improve significantly the prognosis. However, although it is demonstrated that alcohol is related to DCM, the real correlation between specific doses of ethanol, genetic susceptibility and cardiomyopathy development still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In present study genetic study was not possible due to resources limitations. Seth S et al 17 24 . Alcoholic cardiomyopathy (ACM) causes myocyte dysfunction, due to abnormalities in calcium homeostasis, and cause elevated levels of norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies indicating that the effects of alcohol on myocarditis may be reversible. Additionally, significant improvements are determined clinically and echocardiografically in systolic heart functions at least 6 months after the alcohol is given up (9,10,11). Although this situation is presumed to be related to giving up alcohol before the development of fibrosis, it is still in question.…”
mentioning
confidence: 99%